2009
DOI: 10.1093/humrep/dep235
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between attachment, appraisal, coping and adjustment in men and women experiencing infertility concerns

Abstract: Attachment patterns link to couples' relationship satisfaction and are associated with adjustment via appraisal and coping. Identification of such patterns may assist in identifying need and tailoring cognitive interventions to individuals. Participants were mainly white and well-educated, and wider generalization cannot automatically be assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 37 publications
6
70
0
4
Order By: Relevance
“…The Bayley (2009) had represented that couple may have different significantly in using the coping strategies for infertility concern [3]. Greill (1997) suggested that infertile men used the less coping strategies than infertile women in handling infertility because of they experienced the lower distress [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Bayley (2009) had represented that couple may have different significantly in using the coping strategies for infertility concern [3]. Greill (1997) suggested that infertile men used the less coping strategies than infertile women in handling infertility because of they experienced the lower distress [28].…”
Section: Discussionmentioning
confidence: 99%
“…The most infertile couple experience emotional suffering from infertility [2]. For the most couple, infertility is associated with increased distress especially in infertile women and it can endanger the mental health [3]. Infertility associate with mental consequences including anxiety, depression, and psychosomatic complication [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13,16,[36][37][38] Female participants expressed strong emotions about the experience of infertility, using quite striking expressions: "My life would stop," "My world would be destroyed." These intense feelings, and the cultural influences on the meanings assigned to having children, were important aspects of the data.…”
Section: Discussionmentioning
confidence: 99%
“…6,[9][10][11][12] Compared to men, childless women feel more stress and pressure, and have higher rates of anxiety and depression. 8,[10][11][12][13][14][15][16][17][18] The most important reason for this is the loss of a sense of motherhood due to infertility, and a loss of productivity, self-esteem, and genetic continuity. 19,20 In some traditional societies, the number of children determines a woman's status in society.…”
Section: ö öZ Ze Et T Amentioning
confidence: 99%